Magnetic Field Effect on the Characteristics of Large-Volume Glow Discharge in Argon at Low Pressure - S. Hasaani , Abdilrida (Iraqi Journal of Science, 2023)
The magnetic field effect on the current-voltage characteristic curves of glow discharge in argon at low pressures has been experimentally investigated. The electrical discharge was ignited in a stainless steel tapered chamber of a nominal volume of 0.5m3 immersed inside a water-cooled coil capable of delivering a magnetic field of strength B of up to 0.42T. Three water-cooled electrodes were inserted into the chamber up to a point where their tips were 20cm away from the surface of the central column of the chamber. An enhancement of the electric field configuration within the region of the electrode assembly was performed by threading one of the electrodes with stainless circular discs(80mm and 140mm in diameter) in various forms(attached or separated). Depending upon the experimentally operating conditions, different glow discharge voltages and their corresponding currents were recorded with an optimum current of 10A at B= 500G and P= 10-3 mbar. A discharge current of 11.7A was reached as the gas pressure was raised by an order of magnitude at B=10G at d=20cm with very slight changes in the discharge voltage. Experimental results were found to be sensitive to the geometry of the electrode assembly, P, and B. Elevation of cathode surface temperature was recorded and found effective in reducing the pumping down cycle over a process of glow discharge cleaning of the internal chamber surface.